2009
DOI: 10.1002/jmor.10716
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stages until hatching of the Lake Victoria cichlid Haplochromis piceatus (Teleostei: Cichlidae)

Abstract: Because little is known about embryonic developmental stages in any haplochromine cichlid, we describe here a series of normal stages of the Lake Victoria cichlid Haplochromis piceatus. We collected 273 embryos and scored them for 47 morphological characters. The result was an illustrated series of 12 stages from embryonic shield until hatching based on live, fixed, and histological material. We defined each stage according to a single ''key'' character that applied to all embryos of that stage. Other characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…For example, observations of embryos of Victoria Cichlid ( Haplochromis piceatus ) revealed that anal fin condensation occurs first, followed by dorsal fin condensation (de Jong et al, 2009); however, the dorsal fin rays appear first in larvae of Nile tilapia, which has similar anal and dorsal fin ray morphology with H. piceatus (Fujimura and Okada, 2007). Thus, the order of appearance of mesenchymal condensation and fin rays in dorsal and anal fins are inconsistent in these species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, observations of embryos of Victoria Cichlid ( Haplochromis piceatus ) revealed that anal fin condensation occurs first, followed by dorsal fin condensation (de Jong et al, 2009); however, the dorsal fin rays appear first in larvae of Nile tilapia, which has similar anal and dorsal fin ray morphology with H. piceatus (Fujimura and Okada, 2007). Thus, the order of appearance of mesenchymal condensation and fin rays in dorsal and anal fins are inconsistent in these species.…”
Section: Discussionmentioning
confidence: 99%
“…Study of the development of multiple taxa can illuminate our understanding of developmental patterns and mechanisms. Among teleost fishes, there are a number of species that have been developed as models (e.g., zebrafish, sticklebacks, medaka, cichlids), but these species do not begin to encompass the diversity of phenotypes represented by fishes (De Jong, Witte, & Richardson, ; Fujimura & Okada, ; Iwamatsu, ; Kimmel, Ballard, Kimmel, Ullmann, & Schilling, ; Swarup, ). For instance, skull morphology is an ecologically critical trait that varies enormously across teleost fishes, but among the currently established teleost models only cichlids have evolved substantial skull morphological diversity (Albertson & Kocher, ; Liem, ).…”
Section: Introductionmentioning
confidence: 99%
“…Haplochromis piceatus Greenwood & Gee 1969 is used as a typical suction feeding species (ecomorph) with a long, pointed snout and elongate, gracile jaws. The diet of this zooplanktivorous species includes cladocerans, copepods, insect larvae and pupae [30], [31]. In contrast, Haplochromis fischeri Seegers 2008 ( =  Haplochromis sauvagei non Pfeffer 1896: Greenwood 1980) is a typical biter with short and stout jaws.…”
Section: Introductionmentioning
confidence: 99%